Pengaruh Intensitas Penggunaan Media Sosial, Dukungan Orang Tua, dan Konformitas Teman Sebaya terhadap Prokrastinasi Akademik Dalam Penyelesaian Skripsi Mahasiswa - Fiki Rohana; Kristiani Kristiani; Dewi Kusuma Wardani (Journal on Education, 2023)
The purpose of this study was to determine the effect of the intensity of social media use, parental support and peer conformity on academic procrastination in completing thesis in UNS Economics Education students. The research method used was quantitative with a population of UNS Economics Education students in 2017, 2018, and 2019. The sampling technique used Simple Random Sampling with a total sample of 119 respondents. The results of this study indicate that (1) there is a positive and significant influence between the intensity of social media use on academic procrastination in completing thesis for UNS Economics Education students. (2) there is a negative and significant influence between parental support for academic procrastination in completing thesis for UNS Economics Education students. (3) there is a positive and significant influence between peer conformity on academic procrastination in completing thesis for UNS Economics Education students. (4) there is a positive and significant influence between the intensity of social media use and peer conformity and a negative and significant influence between parental support for academic procrastination in completing thesis for UNS Economics Education students.